Distribution of met‐enkephalin, leu‐enkephalin, substance P, neuropeptide Y, FMRFamide, and serotonin immunoreactivities in the optic tectum of the Atlantic salmon (Salmo salar L.) - Vecino, Elena; Ekström, Peter (The Journal of Comparative Neurology, 1990)
The distribution of the neuropeptides methionine‐ and leucine‐enkephalins, substance P, FMRFamide, neuropeptide Y, and vasoactive intestinal peptide, as well as the biogenic amine serotonin was studied in the optic tectum of the Atlantic salmon by means of immunocytochemistry. Peroxidase‐antiperoxidase and indirect immunofluorescence methods were used to compare the differential laminar distribution of each of these substances. Nine parts of the optic tectum were selected for analysis on frontal sections: median, dorsolateral, and ventrolateral areas at rostral, medial, and caudal levels. Methionine‐ and leucine‐enkephalin immunoreactive fibers were found in discrete sublayers in the following strata: stratum opticum, stratum fibrosum et griseum superficiale, stratum griseum centrale, stratum, and album centrale. Most of the substance P‐, serotonin‐, and vasoactive intestinal peptide‐immunoreactive fibers were found in the stratum album centrale, whereas the FMRFamide‐ and neuropeptide Y‐immunoreactive fibers were more or less randomly distributed within most of the strata of the optic tectum. Neuropeptide Y‐immunoreactive cell bodies were located in the stratum periventriculare. We suggest an extrinsic origin for most of the immunoreactive fibers observed in the optic tectum, except for the neuropeptide Y‐immunoreactive fibers that probably originate in the periventricular neurons. Although retinal peptidergic input to the optic tectum has been proposed in other vertebrates, there is no evidence that any of the neuropeptidelike or serotonin immunoreactive fibers in the optic tectum of the salmon should be of retinal origin. Differences and similarities with the distribution of neuropeptides in the optic tectum in representatives of other vertebrate classes are discussed.